The Influence of Understanding Learning Design, Learning Environment, and Student Acceptance on the Teaching Creativity of Driver Teachers at Tanjung Jabung Barat regency - Firmansah Firmansah; Sofyan Sofyan; Raden Ali (Universitas Muhammadiyah Enrekang, 2024)
This study aims to investigate the influence of understanding learning design, optimizing the learning environment, and fostering student acceptance on the creative teaching practices of driver instructors in Tanjung Jabung Barat regency. Specifically, it seeks to explore how driver instructors' comprehension of learning design principles affects their creativity in instructional delivery. Examine the impact of the learning environment, including classroom dynamics, resource availability, and technological integration, on teacher creativity in driver education. Analyze the role of student acceptance and engagement in shaping teacher creativity and innovation within the driver education context. Utilizing a mixed-methods approach, this research will employ qualitative interviews, quantitative surveys, and observational studies. Qualitative interviews will be conducted with driver instructors to gain insights into their perspectives on learning design, the learning environment, and student acceptance. Quantitative surveys will be distributed to gather data on teaching creativity and its determinants. Additionally, observational studies will be conducted in actual classroom settings to observe the dynamics between learning design, the learning environment, student acceptance, and teaching creativity. The analysis revealed significant relationships between understanding learning design, optimizing the learning environment, fostering student acceptance, and teaching creativity among driver instructors. Driver instructors' comprehension of learning design principles positively correlated with their creativity in instructional delivery. Furthermore, the learning environment significantly influenced teacher creativity, with conducive classroom dynamics and resource availability enhancing creativity. Student acceptance also played a crucial role, with higher levels of engagement positively associated with teacher creativity and innovation. This research underscores the importance of understanding learning design, optimizing the learning environment, and fostering student acceptance in promoting teaching creativity among driver instructors. The findings provide valuable insights for the development of evidence-based teacher training programs and curriculum frameworks aimed at enhancing creativity and innovation in driver education instruction. Ultimately, addressing these factors can contribute to the improvement of driver education programs, thereby promoting road safety and responsible driving behaviors in Tanjung Jabung Barat regency and beyond.